A 38- Year Demographic Study of Central and Peripheral Giant Cell Granulomas of the Gaws - Saghafi, Shadi; Zare Mahmoodabadi, Reza; Ghazi, Narges; Javan, Abdollah; Zargari, Mohammad; Mortazavi, Hamed (Journal of Dental School, 2019)
Objective: The purpose of this study was to retrospectively analyze the demographic characteristics of patients with central peripheral giant cell granulomas (CGCGs) / (PGCGs) an Iranian population. Methods: In this 38-year retrospective study, the data were obtained from records of 1019 patients with CGCG and PGCG of the jaws referred to the Department of Oral and Maxillofacial, Pathology, Mashhad University of Medical Sciences, Iran between 1972 and 2010. Information regarding age distribution, gender, location of the lesion and clinical signs and symptoms was documented. Results: A total of 1019 patients were affected by giant cell granuloma lesions (GCGLs) including 435 CGCGs and 584 PGCGs. The mean age was 28.91 ± 18.16. PGCGs and CGCGs had a peak of occurrence in the first and second decade of life respectively. A female predominance was shown in CGCG cases (57.70%), whereas PGCGs were more frequent in males (50.85%). Five hundred and ninety eight cases of all giant cell lesions (58.7 %) occurred in the mandible. Posterior mandible was the most frequent site for both Lesions. The second most common site for PGCG was posterior maxilla (21%), whereas anterior mandible was involved in CGCG (19.45%). The majority of patients were asymptomatic. Patient's age, location (mandible/maxilla) and bleeding were the influential variables on the type of the lesion. Conclusion: Although the CGCGs share some histopathologic similarities with PGCGs, differences in demographic features may be observed in different populations.